Original paperA novel method of ultra-low contrast administration for coronarography and percutaneous coronary intervention using the automatic injector. The need to focus on contrast preservation techniques - Stys, Adam T.; Stys, Tomasz; Recki, Przemysław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Background : Contrast-induced nephropathy (CIN) is becoming a more pertinent issue in coronary percutaneous procedures, as the population at risk grows. Contrast preservation is the first and probably most important step in prevention of CIN, and yet the research focus seems to be on CIN preventing drugs. Aim : We describe a novel method of contrast preservation for coronarography and percutaneous coronary intervention (PCI) based on use of the automatic contrast injector (ACI). The method also uses a standardized approach to catheterization aimed at minimizing contrast load; however, it is the programming of the ACI that allows for the ultra-low contrast dose. We present two cases to illustrate the technique. Material and methods : We have used this standardized protocol successfully for the last 4 years in our cath lab in patients with increased risk of CIN, consistently achieving 10 ml or less of contrast load per coronary case. Our ACI programming protocol is relatively easy to follow. Results and conclusions: We think that use of ACI with appropriate programming should become a preferred, if not standard approach in patients at increased CIN risk. We believe that refocusing on contrast preservation techniques and their distribution throughout the interventional community is of utmost importance for public health.